Basic Comparison and Evaluation of Functionality AC-AC Matrix Converter Concepts for HEV Vehicle - Part II - Branislav Dobrucky; Slavomir Kascak; Michal Prazenica; Roman Konarik (Communications - Scientific letters of the University of Zilina, 2020)
The paper deals with a modeling and simulation of the direct AC-AC propulsion system and compares two matrix converter concepts with five-phase traction induction motors (IM) for the hybrid electric vehicle (HEV). The simulation results of [3x5] matrix converter and 4Q-converter are done using Matlab-Simulink environment. Part I deals with a theoretical study of converter concepts for hybrid electric vehicle, since the configurations of [3x5]+[0x5] matrix converters with five-phase motor(s) have not been analyzed so far. Based on simulation results the comparison and evaluation of the property and quality of the quantities of different type of the matrix powertrain are discussed in Part II.